2019
DOI: 10.1186/s40798-019-0229-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physical Activity Indicators for Children and Youth in Ethiopia: Evidence from the Global Matrix 3.0 Study (2017–2018)

Abstract: Background: Regular physical activity is vital for children's health, well-being, and development. However, evidence is scant about physical activity indicators for children and youth in Ethiopia. This study aimed to assess physical activity indicators among children and youth in Ethiopia.Methods: This study was conducted as part of the Active Healthy Kids Global Alliance's "Global Matrix 3.0" which included 49 countries. Data were collected from December 2017 to April 2018. The country research team included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…(35,36). There is no consensus about a single cutoff point to define PA to prevent overweight and obesity, but one of the main factors contributing to increased adiposity is lower energy expenditure caused by decreased PA (37,38). In this study, the odds of being overweight or obesity among adolescents with higher hours of sedentary behaviors were 6 times more likely than those who did not have a sedentary life.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…(35,36). There is no consensus about a single cutoff point to define PA to prevent overweight and obesity, but one of the main factors contributing to increased adiposity is lower energy expenditure caused by decreased PA (37,38). In this study, the odds of being overweight or obesity among adolescents with higher hours of sedentary behaviors were 6 times more likely than those who did not have a sedentary life.…”
Section: Discussionmentioning
confidence: 68%
“…This could be further limited by the hoot weather condition of the study area. One study has showed that only 28% has the recommended PA level and less than 50% use walk from home to school and this worst in the urban setting ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical inactivity and increasing screen-time among children and adolescents around the world have been well-documented in the previous three decades ( 1 ) and they are two of the leading causes of poor physical fitness among the members of those populations. Likewise, several recognized methodologies actively monitor the physical activity and physical fitness of children and adolescents worldwide ( 2 4 ), however, they are locally oriented, and when it comes to Montenegro, this vital issue has remained unexplored.…”
Section: Introductionmentioning
confidence: 99%